Ethics of Permission in Al-Qur'an Guidance: Dr. Perspective Abdul Hayy Al-farmawi in the Maudu'i Tafsir Method - Asniati, Asniati; Ardiansyah, Ardiansyah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research explores the ethical concept of permission in the Qur'an from the perspective of Dr. Abdul Hayy Al-farmawi through the Maudu'i interpretation approach. In his analysis, permission ethics is not only seen as etiquette, but as a reflection of awareness of the rights and obligations between individuals. Dr. Abdul Hayy emphasized that permission reflects recognition of the existence of God as the giver of rights. Education about consent ethics is emphasized as something that must be taught from an early age, and its relevance in the modern digital era is also discussed. This research also compares Dr. Abdul Hayy with the views of other scholars such as Al-Ghazali, Ibn Sa'di, and others through a comparison table. The research results show that understanding the ethics of permits has deep implications in building harmonious social relations and respect for human rights